2017
DOI: 10.1002/ehf2.12134
|View full text |Cite
|
Sign up to set email alerts
|

Uric acid predicts mortality and ischaemic stroke in subjects with diastolic dysfunction: the Tromsø Study 1994–2013

Abstract: Aims To investigate whether serum uric acid predicts adverse outcomes in persons with indices of diastolic dysfunction in a general population. Methods and resultsWe performed a prospective cohort study among 1460 women and 1480 men from 1994 to 2013. Endpoints were all-cause mortality, incident myocardial infarction, and incident ischaemic stroke. We stratified the analyses by echocardiographic markers of diastolic dysfunction, and uric acid was the independent variable of interest. Hazard ratios (HR) were es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
(48 reference statements)
1
10
1
Order By: Relevance
“…Although a high SUA level might be an epiphenomenon and just serve as a marker of reduced excretion because of renal dysfunction, which may reduce LV contractility, we demonstrated a significant association between SUA levels and LVGLS independent of renal function. Previous studies demonstrated the association between SUA and diastolic parameters in patients with established cardiac disease including HF and cardiomyopathy, 31–33 whereas SUA was not correlated with E/e′ in the present study. This discrepancy might be partially explained by the difference in study population, namely, we included individuals without overt cardiac disease who had relatively preserved diastolic function.…”
Section: Discussioncontrasting
confidence: 75%
“…Although a high SUA level might be an epiphenomenon and just serve as a marker of reduced excretion because of renal dysfunction, which may reduce LV contractility, we demonstrated a significant association between SUA levels and LVGLS independent of renal function. Previous studies demonstrated the association between SUA and diastolic parameters in patients with established cardiac disease including HF and cardiomyopathy, 31–33 whereas SUA was not correlated with E/e′ in the present study. This discrepancy might be partially explained by the difference in study population, namely, we included individuals without overt cardiac disease who had relatively preserved diastolic function.…”
Section: Discussioncontrasting
confidence: 75%
“…A total of 1,522 articles were initially included. After searching the public databases with medical subject terms that were previously defined, there were 19 articles with data on association between SUA and risk of stroke that were eligible for inclusion (11,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36), including 37,386 males and 31,163 females in the final analysis. The detailed selection process including specific reasons for exclusion was tabulated in Figure 1.…”
Section: Eligible Studiesmentioning
confidence: 99%
“…A number of epidemiologic studies have shown that an elevated uric acid level is associated with a wide variety of adverse health outcomes, including hypertension, metabolic syndrome, kidney disease, cardiovascular disease (CVD), and cancer . However, the role of uric acid as an independent risk factor for CVD, cancer, and all‐cause mortality remains a subject of controversy . Some studies demonstrated a positive association between hyperuricemia and cardiovascular mortality , while other studies did not .…”
mentioning
confidence: 99%